The Influence of Self-Assessment System and Tax Socialization on Taxpayer Compliance With Nationalism as A Moderation Variable - Visiana, Khalisah; Susanto, Susanto (Journal Research of Social Science, Economics, and Management, 2023)
The purpose of this study is to determine the influence of the Self-Assessment System, Tax Socialization on Taxpayer Compliance with Nationalism as a moderation variable. Data was collected using a survey method with questionnaire techniques. The population used in this study is every person who is already working and has an NPWP. Samples were taken using purposive sampling. that is the technique of determining samples with certain considerations. These considerations are a WP who has worked and has at least 1 year of work experience, a worker's income level above 4 million, permanent employment status and is not a day worker, age over 20 years and also has an NPWP and understands tax obligations. The results of this study are Self-assessment system on taxpayer Compliance has a significant effect, Tax Socialization does not have a significant effect on taxpayer compliance, Nationalism has a significant effect on Taxpayer Compliance, nationalism moderates the Self-assessment system has an insignificant effect on Taxpayer Compliance, The influence of Nationalism moderates Tax Socialization on taxpayer compliance has a significant effect.